Presier’s disease: idiopathic avascular necrosis of scaphoid in a case presenting with wrist pain in young male - Suthar, Pokhraj P.; Parmar, Gaurav R.; Trivedi, Chinmay; Vithlani, Hemen I. (International Journal of Research in Medical Sciences, 2017)
A 25-years-old male presented with complain of pain in right wrist and difficulty in gripping objects. No history of trauma to the right wrist joint. On local examination, tenderness was present in right anatomical snuff box. Tenderness was elicited by axial compression on right first metacarpal with decreased range of the motion at the right wrist compare to the left side. Routine blood investigation was within normal limits. X-ray of the right wrist joint showed minimal sclerotic in right scaphoid. On MRI right wrist joint, low intensity signal was seen involving the whole right scaphoid bone on T1 weighted, T2 weighted and STIR images with loss of normal marrow signal intensity. So according to the Herbert and Lanzetta it was stage 4 and Kalainov et al, type 1 avascular necrosis. Diagnosis of idiopathic avascular necrosis of the right scaphoid bone was postulated based on clinical and radiological findings. Patient was treated with vascularised pedicle bone graft from the right distal radius. The patient was gradually improved clinically with subsidence of pain and improvement in the grip strength over 1 year.